Poluição costeira e marinha: avaliação, diagnóstico e propostas para enfrentamento e governança - Pinto, Luisa Janaina Lopes Barroso (2023)
Garbage is a serious threat to the ocean, and it is clearly recognized that the capacity to assimilate waste and make it harmless is limited. It is conceived that a preponderant part of the residues found in the marine environment is composed of plastic items, which is related to their wide use by contemporary society, their durability, their buoyancy in the ocean, but mainly due to the improper disposal and handling of solid urban waste. In this scenario, the general objective of the thesis is to evaluate the perverse problem of coastal and marine pollution, as well as its multiple implications. For this purpose, a path was designed to understand the socioeconomic and environmental perspective, through the construction and application of methodological tools, as well as the systematic analysis of the main and perverse waste, plastic, through an analytical structure of the orchestrating network. In this logic, the thesis is divided into three sections in the format of articles: The first article entitled “Marine pollution and socioeconomic vulnerability in Brazilian coastal cities”, assumes that coastal cities are commonly related to vulnerable environments and sensitive to changes, thus, it aims to assess the socioeconomic vulnerability of municipalities on the Brazilian coast as a result of polluting coastal agents. To this end, an exploratory-quantitative study was carried out of the segments of the economy of the sea expressed in their different categories, using secondary information from governmental databases, it was observed that the effects of polluting elements in the Brazilian coast region act by determinants local social and environmental factors that induce effects on economic factors. In the second article “Diagnosis and monitoring of solid debris deposited on a coastal strip”, the objective was to qualitatively evaluate solid debris deposited along a coastal strip in an approach based on Remotely Piloted Aircraft (RPAs). The methodological route was established through drone technology to fly over the same transects in an area of the coastal zone in the extreme northeast of the municipality of Fortaleza, Ceará, Brazil. It was shown that residue mapping using ARPs was influenced by the relationship between flight altitude and residue size. The two unsupervised classification methods, when flying at 10 and 20 m altitude, proved to be effective in mapping solid waste incorrectly deposited in sand strips. Finally, article three “An ocean of plastic: the orchestration of a perverse problem” inferred that a well-orchestrated network is a determining factor for the governance of emerging problems, so the article sought to answer the following questions: The action of plastic waste in oceans fit as a perverse problem in the perception of consumers of marine and coastal resources? In the existence of network confrontation, does the network have solid levels of orchestration to manage the perverse problem? Its objective was to develop an analytical structure using the characteristics defined by Dhanaraj and Parkhe (2006), as a platform for verification in network orchestration. The findings showed that the action of plastic debris in the oceans fits as a perverse problem in the perception of consumers of marine and coastal resources and the network does not have solid levels of orchestration to manage the perverse problem, and that the core of institutional action is better articulated and emerges with orchestrating leaders.